2000
DOI: 10.1034/j.1600-065x.2000.017502.x
|View full text |Cite
|
Sign up to set email alerts
|

Early B-lymphocyte precursors and their regulation by sex steroids

Abstract: This review describes an improved characterization of early B-lymphocyte precursors in mice and the remarkable sensitivity of the same cells to hormones. The nuclear enzyme terminal deoxynucleotidyl transferase (TdT) was used as a marker to image and characterize bone marrow cells lacking all lineage-associated markers. Most early TdT+ precursors have a distinctive density of c-kit and express the interleukin-7Ralpha chain, as well as flt-3/flk2, but lack CD34. An understanding of those cell surface properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 70 publications
(97 reference statements)
1
14
0
Order By: Relevance
“…Sexual hormones, such as oestrogens, regulate lymphopoiesis; pro-B lymphocytes are especially sensitive to high oestrogen concentrations, resulting in decreased numbers of these cells, where oestrogen can arrest lymphoid lineage differentiation [37, 38]. A similar PRL effect may explain the reduced numbers of pro-B cells observed during hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual hormones, such as oestrogens, regulate lymphopoiesis; pro-B lymphocytes are especially sensitive to high oestrogen concentrations, resulting in decreased numbers of these cells, where oestrogen can arrest lymphoid lineage differentiation [37, 38]. A similar PRL effect may explain the reduced numbers of pro-B cells observed during hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is a potent regulator of B lymphopoiesis at a very early stage. (5) Because B cells at multiple stages of differentiation can express bone-remodeling related cytokines, including RANKL, (37) changes in early B cells with estrogen deficiency may affect osteoclastogenesis and subsequent bone loss. Ishimi et al (38) reported that genistein completely inhibited the increase in bone loss and B-lymphopoiesis induced by ovariectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, newly formed B cells and pre-B cells are noticeably depressed in pregnant or estrogen-treated mice. (5) Furthermore, various cytokines, such as interleukin (IL)-6, IL-7, tumor necrosis factor (TNF)α and TNFβ are involved in the growth and differentiation of hemopoietic cells, and most of these cytokines are also involved in bone remodeling. (6) Miyaura et al (7) showed that changes in both B-lymphopoiesis and bone mass in IL-7-treated female mice were similar to those in ovariectomized (OVX) mice.…”
Section: Introductionmentioning
confidence: 99%
“…First, oestrogen is involved in proliferation and differentiation of normal haematopoietic cells (Kincade et al , 2000; Kouro et al , 2001; Medina et al , 2001). Second, binding sites for oestrogen have been reported in primary leukaemias (Danel et al , 1985) and leukaemia cell lines (Kauss et al , 2008).…”
Section: Discussionmentioning
confidence: 99%